Structure determination of Fe-Al-Ge alloys. (November 2015) - Gargicevich, D; Josa, V M Galván; Blanco, C; Lambri, A; Cuello, G J
Abstract: We studied the crystalline structure of Fe - 8at.%Al - 4at.%Ge alloy between 300 and 1300 K and its relation to the mechanical response by means of neutron diffraction and mechanical spectroscopy. At room temperature we observe a Fe3 Al-type ordered structure with a deficiency of Al in the 8c sites. The Ge atoms are distributed in the 4a and Al atoms in 8 c sites. At high temperature we observe an order-disorder transformation when the crystal structure becomes Fe-α type. This loss of order gives rise to the hysteresis behavior of damping between the heating and cooling runs.